2021
DOI: 10.3390/fermentation7040306
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Soybean Meal Fermentation for Aqua-Feed with Bacillus subtilis natto Using the Response Surface Methodology

Abstract: This study aimed to improve the nutritional value of soybean meal (SBM) by solid-state fermentation (SSF) using Bacillus subtilis natto (B. s. natto) to overcome the limitations of SBM usage in aquafeed. The response surface methodology (RSM) was employed to explore the relationships of fermentation conditions, such as temperature, time, water-substrate ratio, and layer thickness, on the degree of protein hydrolysis (DH) and the crude protein (CP) content. The optimum conditions for achieving the higher DH (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…had improved free amino acids, which may be attributed to the higher exogenous protease enzyme activity, secreted through microbial fermentation [ 48 ]. In concurrence with the current study, Zhang et al [ 16 ] reported improvement of total crude protein, total essential and nonessential amino acids and total free amino acids. Similar data obtained by Gerham et al [ 49 ] for fermented soybean meal showed it higher total essential, nonessential and free amino acids that lead to improve these amino acids ileal and standard digestibility in growing swine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…had improved free amino acids, which may be attributed to the higher exogenous protease enzyme activity, secreted through microbial fermentation [ 48 ]. In concurrence with the current study, Zhang et al [ 16 ] reported improvement of total crude protein, total essential and nonessential amino acids and total free amino acids. Similar data obtained by Gerham et al [ 49 ] for fermented soybean meal showed it higher total essential, nonessential and free amino acids that lead to improve these amino acids ileal and standard digestibility in growing swine.…”
Section: Discussionsupporting
confidence: 92%
“…The second stage of fermentation we used Bacillus subtilis SB102 (CGMCC1.769) using the directions of Zhang et al [ 16 ] for preparation of B. subtilis ; inoculum was developed in Luria-Bertani (LB) at 37 °C for 48 h. Then, the inoculum was adjusted to 10 8 CFU /mL using uncontaminated physiological saline. After 24 h fermentation of soybean meal by Asperigillus oryzae, an inoculum of B. subtilis was mixed with the fermented mixture with 10 8 CFU/ 100 g and incubated at 37 °C for 36 h.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies show that fermentation with B. subtilis natto isolates ( 44 ) could increase the value of the DH (15.96%) and CP (55.76%) of SBM. Similarly, CP in the SBM was increased by 8.37 and 0.34% when fermented with B. subtilis and A. oryzae , respectively, ( 45 ).…”
Section: Discussionmentioning
confidence: 97%
“…The temperature of the fermentation system can also affect the activity of enzymes (Zhang et al ., 2020). For example, when the temperature was raised from 28 °C to 43 °C, the degree of hydrolysis of the proteins fermented with Bacillus natto increased, resulting in a constantly rising fermentation rate (Zhang et al ., 2021). Salt concentration is another key environmental factor that influences the fermentation of soybean meal.…”
Section: Microbial Fermentation Of Soybean Mealmentioning
confidence: 99%
“…Similarly, Zhang et al . (2021) found that the free amino acid content of fermented soybean meal was 12.76 times higher than soybean meal. Furthermore, De Olmos & Garro (2020) used lactic acid to ferment soybean meal and successfully obtained free amino acid products with high biological activity.…”
Section: The Main Composition Of Fermented Soybean Mealmentioning
confidence: 99%